Prinsip Keluasan Syartul Waqif Dalam Membangunkan Tanah Wakaf Khas - Nor Amni Bazilah Binti Mohd Zain; Muaz Bin Mohd Ghani Basri; Fuadah Johari (Kolej Universiti Islam Perlis (KUIPs), 2024)
Non-Indexed Publication